THE SPANISH EXILES OF THE CIVIL WAR IN THE HIGH CENTERS OF ECONOMICS EDUCATION OF LATIN AMERICA - Rodríguez, Manuel Martín (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
At the end of the Spanish civil war (1936-39), many intellectual people were in the exile. In spite of that did not exist still in Spain high studies of Economy in those dates, enough of them became teachers of this discipline or being employers at centers of economic research. In this article it is very important to study the main contributions of this group, very little known till now, about the education and research of Economy in Latin America.